The Impact of Oil Prices on Inflation: The Case of Azerbaijan - Mukhtarov, Shahriyar; Mammadov, Jeyhun; Ahmadov, Fariz (International Journal of Energy Economics and Policy, 2019)
This paper investigates the relationship between inflation, oil prices and exchange rate in Azerbaijan using the Vector Error Correction Model (VECM) to the data ranging from 1995 to 2017. The results from cointegration method confirm the existence of a long-run relationship among the variables. Moreover, estimation results of VECM show that the oil prices and exchange rate have positive and statistically significant impact on inflation in the long-run. This implies that 1% increase in oil prices and exchange rate increases inflation by 0.58% and 1.81%, respectively. Results of the study also reveal that inflation is observed during the periods of both high and low oil prices, and the exchange rate acts as the transmission channel from oil prices to inflation. Keywords: Inflation, Oil Price, Exchange Rate, VECM, Azerbaijan JEL Classifications: E31, Q4 DOI: https://doi.org/10.32479/ijeep.7712